Vital statistics for restoring true academia. - Shuib, Munir (National Higher Education Research Institute, Universiti Sains Malaysia, 2010)
The global expansion of access to higher education and its influence on renewed interest in global and national university ranking has prompted Malaysian universities to relook and rethink about academic quality. Restoring or improving the academic standards of universities has to start with an analysis of the inherent quality of academics. Little has been done hitherto to systematically address the quality of academics in the local context. Hence, an empirical exploration of students’ perception of lecturers in a local public university was carried out. The small questionnaire survey (n=69) gauged students’ candid views on the attributes, attitudes and aptitude of lecturers with respect to effective instruction. The caveat here is that the data is from responses of science students only.